Apnea after Routine Eye Examinations in Premature Infants - Reid, Brittany; Wang, Hongyue; Guillet, Ronnie (American Journal of Perinatology, 2017)
Objective To determine the frequency of cardiorespiratory events following routine exams for retinopathy of prematurity (ROP).Study Design This is a retrospective review of 79 premature infants in the neonatal intensive care unit at the University of Rochester Medical Center. The baseline for each infant (mean cardiorespiratory events in the 72 hours before the exam) was compared with the number of cardiorespiratory events during the subsequent 24 hours using generalized estimating equation and the Mantel–Haenszel chi-square test to determine if there was an association between cardiorespiratory events and potential risk factors.Results Approximately 19 to 25% of infants experienced an increase in cardiorespiratory events in the 24 hours following their eye exams. These newborns were generally of a younger gestational age and lower birthweight.Conclusion The frequency of cardiorespiratory events following routine ROP exams is similar to that following routine immunizations in this population. Thus, in infants being continuously monitored during the 24 hours after the exam, alterations in medical care in the absence of other clinical signs suggestive of sepsis or clinical deterioration may not be required, limiting unnecessary antibiotic exposure, prolonged caffeine administration, unwarranted gastroesophageal reflux treatment, and undue family stress.
Keywords: apnea of prematurity; retinopathy of prematurity; prematurity